Evidence of duration and type of illness in children found unexpectedly dead. Issue 6 (June 1976) - Sinclair-Smith, C; Dinsdale, F; Emery, J
Abstract : The thymus, rib, and liver from a series of 200 children found unexpectedly dead showed that in over 90% of these children the costochondral junction indicated that a retardation in growth velocity had preceded death. In a similar proportion of children the liver showed fatty change indicating a metabolic upset, which in 5% was of severe degree. Changes in the thymus compatible with a normal reaction to infection were observed in only a little over half of the child deaths. An absence of gross thymic reaction in some children in whom there was other evidence of infection suggests that in some an abnormal immunological reaction was taking place. It is concluded that careful systematic clinical monitoring of growth in these children would have shown abnormality in nearly all.